Actions do not clearly impact auditory memory - Font-Alaminos, Marta; Paraskevoudi, Nadia; SanMiguel, Iria (Frontiers in Human Neuroscience, 2023)
When memorizing a list of words, those that are read aloud are remembered better than those read silently, a phenomenon known as the production effect. There have been several attempts to understand the production effect, however actions alone have not been examined as possible contributors. Stimuli that coincide with our own actions are processed differently compared to stimuli presented passively to us. These sensory response modulations may have an impact on how action-revolving inputs are stored in memory. In this study, we investigated whether actions could impact auditory memory. Participants listened to sounds presented either during or in between their actions. We measured electrophysiological responses to the sounds and tested participants’ memory of them. Results showed attenuation of sensory responses for action-coinciding sounds. However, we did not find a significant effect on memory performance. The absence of significant behavioral findings suggests that the production effect may be not dependent on the effects of actions per se. We conclude that action alone is not sufficient to improve memory performance, and thus elicit a production effect.